Exosomal microRNAs as Potential Biomarkers and Therapeutic Agents for Acute Ischemic Stroke: New Expectations - Xu, Yingzhi; Hu, Yue; Xu, Shixin; Liu, Fengzhi; Gao, Ying (Frontiers in Neurology, 2022)
The morbidity and mortality rates of ischemic stroke (IS) are very high, and IS constitutes one of the main causes of disability and death worldwide. The pathogenesis of ischemic stroke includes excitotoxicity, calcium overload, oxygen radical injury, inflammatory reactions, necrosis/apoptosis, destruction of the blood-brain barrier (BBB), and other pathologic processes. Recent studies have shown that exosomes are critical to the pathogenesis, diagnosis, and treatment of cerebral infarctions resulting from ischemic stroke; and there is growing interest in the role of exosomes and exosomal miRNAs in the diagnosis and treatment of IS. Exosomes from central nervous system cells can be found in cerebrospinal fluid and peripheral bodily fluids, and exosomal contents have been reported to change with disease occurrence. Exosomes are small membranous extracellular vesicles (EVs), 30–150 nm in diameter, that are released from the cell membrane into the depressions that arise from the membranes of multivesicular bodies. Exosomes carry lipids, proteins, mRNAs, and microRNAs (miRNAs) and transport information to target cells. This exosomal transfer of functional mRNAs/miRNAs and proteins ultimately affects transcription and translation within recipient cells. Exosomes are EVs with a double-membrane structure that protects them from ribonucleases in the blood, allowing exosomal miRNAs to be more stable and to avoid degradation. New evidence shows that exosomes derived from neural cells, endothelial cells, and various stem cells create a fertile environment that supports the proliferation and growth of neural cells and endothelial cells, inhibits apoptosis and inflammatory responses, and promotes angiogenesis. In the present review, we discuss how circulating exosomes—and exosomal miRNAs in particular—may provide novel strategies for the early diagnosis and treatment of ischemic stroke via their potential as noninvasive biomarkers and drug carriers.